IMPLEMENTASI PROTOKOL HANDOVER SBAR UNTUK MENINGKATKAN KESELAMATAN PASIEN RISIKO TINGGI PREEKLAMPSIA DI UPT PUSKESMAS SIBULUE - Mulfiyanti, Dewi; Andi Satriana,; Megawati, Megawati; Fitrah Ramadani, (Nusantara Hasana Journal, 2026)
Preeclampsia is a leading cause of maternal death and requires timely treatment. Communication failures during patient handovers often lead to delays in clinical intervention. The purpose of this study was to analyze the effect of implementing the SBAR communication model on the quality of handover information and the safety of preeclampsia patients. This study used a quasi-experimental design (pre-posttest) with 30 healthcare workers in the maternal care unit using a total sampling technique. The results showed that SBAR implementation significantly improved the accuracy of clinical data (p < 0.05), particularly in the Assessment and Recommendation components. Patient safety incidents decreased dramatically from 14 cases to 1 case during the observation period. The conclusion of this study is that the SBAR protocol effectively improves the quality of communication and the safety of preeclampsia patients through more structured early risk detection.